The Implementation of The Time Token Arends Learning Model on Student Learning Activeness in Fiqh Subjects - Hasnah, Radhiatul; Zukdi, Iilpi; Adriantoni, Adriantoni; Utami, Sry (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2024)
This study aimed to determine the influence of student learning activeness using the Time Token Arends learning model on student learning activeness class in Fiqh subjects at a Private junior high school or boarding school. This study used an experimental method with a quantitative design. The study used sample random sampling as a technique to take the experiment class and control class. The results of this study were (1) The pre-test of the control class has a low category in learning activeness with a mean of 34.03. (2) The pre-test of the Experiment class had a low category with a mean of 38,42 in learning activeness. (3) The post-test of student learning activeness in the control class was the low category with a mean of 40,36. It was a higher mean than the pre-test mean in the control class. (4) The post-test of the experiment class in learning activeness had a low category with a mean of 45,97. Meanwhile, the post-test mean was higher than the pre-test mean. It can be concluded that Time Token Arends influenced students' learning activeness in the seventh class in Fiqh subjects at a Private junior high school or boarding school in West Pasaman Barat